Ethics 4.0: Ethical dilemmas in healthcare mediated by social robots - Soares, A.; Piçarra, N.; Giger, J.-C.; Oliveira, R.; Arriaga, P. (International Journal of Social Robotics, 2023)
This study examined people's moral judgments and trait perceptions toward a healthcare agent's response to a patient who refuses medication. A sample of 524 participants was randomly assigned to one of eight vignettes in which the type of healthcare agent (human vs. robot), the use of a health message framing (emphasizing health-losses for not taking vs. health-gains in taking the medication), and the ethical decision (respect the autonomy vs. beneficence/nonmaleficence) were manipulated to investigate their effects on moral judgments (acceptance and responsibility) and traits perception (warmth, competence, trustworthiness). The results indicated that moral acceptance was higher when the agents respected the patient's autonomy than when the agents prioritized beneficence/nonmaleficence. Moral responsibility and perceived warmth were higher for the human agent than for the robot, and the agent who respected the patient’s autonomy was perceived as warmer, but less competent and trustworthy than the agent who decided on the patient’s beneficence / nonmaleficence. Agents who prioritized beneficence/nonmaleficence and framed the health gains were also perceived as more trustworthy. Our findings contribute to the understanding of moral judgments in the healthcare domain mediated by both healthcare humans and artificial agents.